A Focal Point of Coordination: A Case Study of the ASEAN-Indonesia National Secretariat’s Coordination Efforts - Jaya, Janita (JAS (Journal of ASEAN Studies), 2025)
The research assessed the internalization of the 2007 Charter of the Association of Southeast Asian Nations or the ASEAN Charter into national legislation, particularly on the mandate stipulated in Article 13, to establish an ASEAN National Secretariat for each ASEAN member state. The case study provided an overview of the ASEAN-Indonesia National Secretariat, to examine the regional-level to national-level policy transfer of ASEAN cooperation adopted by the Indonesian government and demonstrates the democratic foreign policy-making process in Indonesia. A qualitative content analysis was applied to assess the official and legal documents regarding the ASEAN-Indonesia National Secretariat. The research finds that the Indonesian statutory provisions stipulate that the ASEAN-Indonesia National Secretariat is a focal point of coordination for ASEAN cooperation in Indonesia, where the Indonesian Ministry of Foreign Affairs is the main supporting unit and functions as a public relation for advocating ASEAN awareness of the Indonesian people. The study is expected to contribute to the literature on international relations and public administration, where Indonesia’s experience in constructing a coordinated policy network among governmental institutions for the implementation of ASEAN regional commitments in domestic settings could be a model for other ASEAN member states or other regional framework.